Ghrelin–LEAP2 interactions along the stomach–liver axis - Katsuya Sakai; Yuki Nakazato; Yuki Shiimura; Weidong Zhang; Masamitsu Nakazato (Endocrine Journal)
Ghrelin produced in the stomach promotes food intake and GH secretion, and acts as an anabolic peptide during starvation. Ghrelin binds to the growth hormone secretagogue receptor, a G protein-coupled receptor (GPCR), whose high-resolution complex structures have been determined in the apo state and when bound to an antagonist. Anamorelin, a low-molecular-weight ghrelin agonist, has been launched in Japan for the treatment of cancer cachexia, and its therapeutic potential has attracted attention due to the various biological activities of ghrelin. In 2019, liver-expressed antimicrobial peptide (LEAP2), initially discovered as an antimicrobial peptide produced in the liver, was identified to be upregulated in the stomach of diet-induced obese mice after vertical sleeve gastrectomy. LEAP2 binds to the GHSR and antagonizes ghrelin’s activities. The serum concentrations of human LEAP2 are positively correlated with body mass index, body fat accumulation, and fasting serum concentrations of glucose and triglyceride. Serum LEAP2 elevated and ghrelin reduced in obesity. Ghrelin and LEAP2 regulate body weight, food intake, and GH and blood glucose concentrations, and other physiological phenomena through their interactions with the same receptor, GHSR.